The Most Common Nursing Diagnoses Enforced in Diabetes Mellitus Patients with Complications - Puspita, Annisa Mega; Yulanda, Nita Arisanti; Rahmah, R.A Gabby Novikadarti (Universitas Malahayati, 2024)
ABSTRACT Diabetes mellitus has been one of the world's medical emergencies, with the fastest-growing prevalence this century. To overcome public health problems, nurses have an important role in providing optimal services based on an established standard of nursing care. One of the important components of nursing care is nursing diagnosis, which is the basis of nursing decision-making. This study aimed to describe the most common nursing diagnoses in patients with diabetes mellitus. The research design used was a descriptive study with a retrospective approach. The population in this study was the medical records of patients with diabetes mellitus who were admitted to the inpatient room on January 2024, totaling 104 medical records with consecutive sampling techniques. The data collection tool used was an observation sheet. The analysis technique used, namely univariate analysis, includes frequency distribution and percentage of nursing diagnoses enforced on clients with a medical diagnosis of diabetes mellitus. The results of this study found that there were 19 nursing diagnoses enforced by nurses in patients with diabetes mellitus, consisting of actual nursing diagnoses (93.2%) and risk nursing diagnoses (6.8%). The six most common nursing diagnoses in patients with diabetes mellitus are acute pain (35.6%), skin/tissue integrity disorders (14.4%), activity intolerance (10.6%), ineffective breathing patterns (7.7%), chronic pain (5.8%), and ineffective peripheral perfusion (5.8%). It can be concluded that most of the nursing diagnoses enforced in patients with diabetes mellitus are not only caused by the clinical condition of diabetes mellitus but also by complications that accompany the condition of diabetes mellitus itself. For future researchers, hopefully, it can develop research into a broader scope, such as conducting bivariate analyses of factors related to the enforcement of nursing diagnoses in diabetes mellitus patients with complications. Keywords: Nursing Diagnosis, SDKI, Diabetes Mellitus